A kind of acid and alkali resistant nanofiltration membrane and preparation method thereof
By introducing carboxybutyrib structure and epoxy-polyethylene glycol-epoxy into the polyamide separation layer of the nanofiltration membrane, a highly crosslinked network structure is formed, which solves the problem of degradation in the performance of the nanofiltration membrane during acid-base cleaning, and achieves higher acid-base resistance and longer service life.
Patent Information
- Application Number
- CN202310001891.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-01-03
AI Technical Summary
Existing nanofiltration membranes are prone to deterioration in the acid-base cleaning process, and long-term acid-base cleaning will damage the structure of the separation layer and lead to irreversible performance losses.
By adding carboxybutyronitrile latex to the aqueous phase and adding epoxy-polyethylene glycol-epoxy to the organic phase as a crosslinking agent for interfacial polymerization, the carboxyronitrile structure is crossed into the polyamide separation layer to form a highly crosslinked complex network structure, which improves the molecular weight and acid and alkali resistance of the polyamide layer.
The stability and separation performance of nanofiltration membranes in acid-base cleaning environments are improved, the service life of the membrane is extended, the preparation process is simplified, and the production process is easy to be produced in an industrial manner.
Smart Images

Figure BDA0004034263870000091 
Figure BDA0004034263870000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment membranes, and in particular relates to an acid- and alkali-resistant composite nanofiltration membrane and a preparation method thereof. Background Art
[0002] In recent years, membrane technology has played an increasingly important role in gas separation, aqueous solution separation, separation and purification of chemical products and biochemical products, and has been widely used in food and beverage processing, industrial wastewater treatment, large-scale gas separation, hydrometallurgical technology and other fields. Nanofiltration membrane is an important branch of membrane technology, with a molecular weight cutoff between 200-2000 and a multi-charged surface. Under the combined action of multiple mechanisms such as pore size screening and Donan effect, nanofiltration membrane has a selective separation effect on monovalent and multivalent salt ions, and has different interception effects on organic matter of different molecular weights. It has been widely used in chlor-alkali denitrification, lithium extraction from salt lakes, municipal water treatment, concentration and purification of pharmaceutical active substances, and seawater desalination pretreatment.
[0003] In the actual application of nanofiltration membranes, various pollutants will gradually deposit on the surface of the membrane, causing membrane pollution and reducing the performance of the nanofiltration membrane. In order to prevent the influence of membrane pollution on the operation of the system, the nanofiltration membrane needs to be cleaned regularly, and membrane cleaning is mainly acid-base cleaning. At the same time, long-term acid-base cleaning will destroy the separation layer structure of the nanofiltration membrane and cause irreversible performance degradation. Therefore, improving the acid-base cleaning resistance of the nanofiltration membrane is one of the important means to maintain the long-term stable operation of the nanofiltration membrane.
[0004] In order to improve the acid and alkali cleaning resistance of nanofiltration membranes, two methods are mainly used in the currently published patents. The first method is to modify the base membrane of the nanofiltration membrane, directly select the base membrane with high physicochemical stability, and then prepare an acid and alkali resistant composite nanofiltration membrane. The second method is to use a polymer with acid and alkali resistance to make a separation layer through surface coating or chemical cross-linking, and the final nanofiltration membrane has acid and alkali resistance. The following examples are given.
[0005] In terms of using a base membrane with high physicochemical stability, CN112007513A discloses a method for preparing a meta-aramid-based polyamide composite nanofiltration membrane, wherein a meta-aramid polymer is coated on a non-woven fabric by a phase inversion method to prepare a meta-aramid porous base membrane, and then a traditional interfacial polymerization reaction is performed to obtain a polyamide composite nanofiltration membrane. The prepared nanofiltration membrane is resistant to acid and alkali corrosion, solvents, has a long service life, and has excellent separation capabilities. CN112495192A discloses a modified polytetrafluoroethylene nanofiltration membrane, which uses polytetrafluoroethylene, which is solvent-resistant, acid-resistant, and has strong physicochemical stability, as a base membrane, and then an interfacial polymerization reaction is performed to prepare a nanofiltration membrane with high desalination, high flux, and acid and alkali resistance. CN113600040A discloses a reverse osmosis membrane, which is prepared by coating a mixed solution of a benzene compound containing amino and sulfonic acid groups, poly-2-ethyl-2-oxazoline and polyethylene glycol diglycidyl ether on a hydrophilic polyethylene porous support layer, heating the solution to react and then performing interfacial polymerization to improve the flux and desalination of the reverse osmosis membrane. The above method performs interfacial polymerization after modifying the base membrane or preparing the interfacial layer, does not directly participate in the construction of the polyamide cross-linked network structure, and the improvement of acid and alkali resistance is subject to certain limitations.
[0006] In terms of using acid- and alkali-resistant polymers to directly prepare separation layers, CN105435656A discloses a composite nanofiltration membrane, wherein the separation layer contains a hydroxyl polymer and a silane coupling agent containing a mercapto group, and then forms a mesh structure initial composite membrane after cross-linking reaction, and then is treated with an aqueous solution containing an oxidant to obtain a composite nanofiltration membrane, the nanofiltration membrane can stably operate in an aqueous solution of pH = 0-14, and has strong acid and alkali resistance. CN104548970A discloses a nanofiltration membrane, wherein the separation layer includes a polycation layer and a polyanion layer stacked in sequence, and the polyanion layer contains a sulfonated polyarylethersulfone structure, and the nanofiltration membrane can have excellent separation layer, water permeability and acid and alkali corrosion resistance. CN111001311B discloses a method for preparing a high desalination reverse osmosis membrane, wherein the polyethylene glycol epoxide is coated on the surface of the primary polyamide layer by reacting the epoxy groups of multi-arm polyethylene glycol epoxide with the unreacted amino groups of polyamide, thereby improving the desalination rate of the reverse osmosis membrane. However, polyethylene glycol epoxide does not directly participate in the interfacial polymerization process, and the effect of improving the acid-base stability of the polyamide main network structure is insufficient. CN102921310A discloses a method for preparing a cellulose nanofiltration membrane, using a multifunctional epoxide to modify the surface of a commercial cellulose ultrafiltration membrane, and reacting the hydroxyl groups in the anhydroglucose unit with a multifunctional cross-linking agent to obtain a hydrophilic nanofiltration membrane resistant to organic solvents, achieving a 90% removal rate for 0.1% raffinose in an isopropanol system. Limited by the inferior acid-base resistance of the cellulose material itself, its stability under acid-base shock is limited.
[0007] Based on the current research hotspot of acid- and alkali-resistant nanofiltration membranes, it is necessary to propose a new method for modifying the composite nanofiltration membrane prepared by the traditional interfacial polymerization method, so as to improve the acid- and alkali-resistant performance of the composite nanofiltration membrane while ensuring the separation characteristics of the nanofiltration membrane. Summary of the invention
[0008] The object of the present invention is to provide an acid- and alkali-resistant nanofiltration membrane and a preparation method thereof to solve the above technical problems. By adding carboxylated nitrile latex to the aqueous phase and epoxy-polyethylene glycol-epoxy to the organic phase as a crosslinking agent for interfacial polymerization, the carboxylated nitrile structure is firmly interlaced in the polyamide separation layer to form a highly crosslinked complex network structure, further increasing the molecular weight of the polyamide layer and improving the performance of resisting acid and alkali attacks.
[0009] Another object of the present invention is to provide a method for preparing the above-mentioned nanofiltration membrane, which has a simple and easy process.
[0010] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0011] A nanofiltration membrane resistant to acid and alkali comprises a polysulfone porous support layer and a polyamide separation layer formed on the support layer; wherein the separation layer is made by interfacial polymerization of an aqueous phase containing aliphatic polyamine and carboxyl nitrile latex and an organic phase containing aromatic polyacyl chloride and epoxy-polyethylene glycol-epoxy.
[0012] The method for preparing the acid- and alkali-resistant nanofiltration membrane of the present invention comprises the following steps:
[0013] 1) preparing the aqueous phase: uniformly mixing the aliphatic polyamine, the carboxyl nitrile latex and water to obtain an aqueous phase solution;
[0014] 2) preparing the oil phase: mixing the aromatic polyacyl chloride, epoxy-polyethylene glycol-epoxy and an organic solvent to obtain an oil phase solution;
[0015] 3) Interfacial polymerization reaction: the polysulfone porous support layer is first contacted with the aqueous solution for 2 to 10 minutes, and then contacted with the oil phase solution after removing the excess solution on the surface, and placed in an oven at 100 to 180° C. for 5 to 20 minutes to allow the epoxy to fully react with the amino group and the carboxyl group, and then dried to obtain the nanofiltration membrane.
[0016] Furthermore, in the aqueous phase solution, the mass concentration of the aliphatic polyamine is 1-2.5%, preferably 1.2-1.5%.
[0017] Furthermore, in the aqueous phase solution, the mass concentration of the carboxyl nitrile latex is 0.01-0.05%, preferably 0.02-0.04%.
[0018] Furthermore, the number average molecular weight of the carboxyl nitrile latex is 10,000 to 50,000.
[0019] Furthermore, the aliphatic polyamine is selected from one or more of piperazine (PIP), ethylenediamine, triethylenetetramine, tetraethylenepentamine and aminoethylpiperazine, preferably piperazine.
[0020] Furthermore, in the oil phase solution, the mass concentration of the aromatic polyacid chloride is 0.1-0.25%, preferably 0.15-0.2%.
[0021] Furthermore, in the oil phase solution, the mass concentration of epoxy-polyethylene glycol-epoxy is 0.1-0.5%, preferably 0.2-0.4%.
[0022] Furthermore, the number average molecular weight of the epoxy-polyethylene glycol-epoxy is 1000-5000, preferably 2000-4000.
[0023] Furthermore, the aromatic polyacyl chloride is selected from one or more of trimesoyl chloride, phthaloyl chloride and isophthaloyl chloride, preferably trimesoyl chloride (TMC).
[0024] Furthermore, the organic solvent is selected from one or more of n-hexane, n-heptane, n-decane, Isopar L and Isopar G isomeric alkanes.
[0025] Furthermore, in step 3), the contacting method of the polysulfone porous supporting layer with the water phase and the oil phase can be immersion, surface coating, surface pouring, etc.
[0026] Furthermore, in step 3), after the polysulfone porous support layer contacts the water phase, the excess solution can be removed by using a rubber roller or an air knife to remove excess water on the surface.
[0027] The epoxy-polyethylene glycol-epoxy of the present invention is a linear bifunctional PEG reagent with two epoxy groups. Carboxylic butadiene-acrylonitrite latex is an anionic high molecular polymer emulsion. In the present invention, while the amino group and the acyl chloride undergo interfacial polymerization, the epoxy-polyethylene glycol-epoxy plays a role similar to that of a crosslinking agent, and its epoxy group reacts with the amino group of the aliphatic polyamine and the carboxyl group of the carboxylic butadiene nitrile. The carboxylic butadiene nitrile structure crosses in the polyamide network structure during the interfacial polymerization process, and forms an interwoven complex network structure with the polyamide, and forms a complete separation layer on the polysulfone porous support layer. The introduction of the butadiene nitrile structure in the polyamide separation layer improves the rigidity and crosslinking degree of the polymer network structure, and in an acid-base cleaning environment, it is less likely to be attacked by strong acid and strong base amide bonds, so that the membrane is prevented from gradually losing its separation ability, and the stability of the polyamide separation layer is improved, and the stability of long-term operation can be guaranteed during use.
[0028] Compared with the existing disclosed technology, the positive effects of the present invention are:
[0029] (1) Through the reaction of epoxy groups with amino groups and carboxyl groups, the carboxyl nitrile structure is interwoven in the polyamide network to form a stable network structure with a high degree of cross-linking. The introduction of the carboxyl group of the carboxyl nitrile improves the hydrophilicity of the polyamide separation layer, achieving a high retention rate and high water flux.
[0030] (2) After the same accelerated acid-base cleaning intensity evaluation, the flux and retention rate of the nanofiltration membrane were better stabilized, and the tolerance of the nanofiltration membrane to acid-base cleaning was improved.
[0031] (3) The nanofiltration membrane prepared by the present invention has a simple preparation process, which is highly close to the industrial process and can be easily realized in industrial large-scale production. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0033] The main raw materials used in the specific implementation of the present invention are shown in Table 1.
[0034] Table 1 Main raw materials
[0035] Raw material name Parameters Manufacturer Anhydrous piperazine Purity ≥99% Aladdin Reagent Trimesoyl chloride Purity ≥99% Sanlibenno Carboxylated nitrile latex Number average molecular weight 5000-60000 Yatai Chemical Epoxy-Polyethylene Glycol-Epoxy Number average molecular weight 500-6000 Kaixin Biotechnology Magnesium sulfate Purity ≥98% Xilong reagent
[0036] The separation performance of the prepared nanofiltration membrane is mainly evaluated by two characteristic parameters, namely the water flux and salt retention rate of the membrane.
[0037] Water flux (LMH) is defined as the volume of water that passes through the effective membrane area per unit time under certain operating pressure conditions.
[0038] Salt retention rate calculation formula: R = (1 – C p / C f )×100%, where R represents the interception rate, C f and C p are the salt concentrations (ppm) in the permeate and feed solutions, respectively.
[0039] The test conditions for the separation performance of the membrane refer to the nanofiltration membrane test method in GB / T 34242-2017, but the test conditions are different. The test conditions for the separation performance of the membrane of the present invention are: the feed liquid is a 2000 ppm MgSO4 solution, the feed liquid temperature is 25°C, and the operating pressure is 0.69 MPa (gauge pressure).
[0040] The evaluation of the acid and alkali cleaning resistance of the nanofiltration membrane is based on the actual acid and alkali cleaning conditions. The degradation process of the separation layer of the nanofiltration membrane by acid and alkali is accelerated by increasing the acid and alkali concentration and temperature. The estimated service life of the nanofiltration membrane can be quantitatively detected by calculating the decrease in the membrane retention rate after accelerated acid and alkali cleaning. That is, the greater the absolute value of the decrease in the retention rate after cleaning, the shorter the estimated service life of the membrane. In order to better understand this test method, the accelerated evaluation steps of the acid and alkali cleaning resistance are briefly described as follows.
[0041] (1) Solution preparation: Prepare a 2000 ppm MgSO4 aqueous solution and adjust its pH to 7.0±0.5 with NaOH as the initial performance test stock solution; prepare 1 mol / L HCl and 0.5% NaOH solutions and place them in the acid and alkali tanks, respectively, as acid and alkali cleaning solutions;
[0042] (2) Acid cleaning performance test: After the membrane that has undergone the initial performance test is washed with a 35°C HCl solution in a cross-flow manner for 10 hours, the difference in flux and retention rate before and after acid washing is tested and calculated;
[0043] (3) Alkali cleaning resistance test: After the membrane that has undergone the initial performance test is flushed with a 35°C NaOH solution for 10 hours, the difference in flux and retention rate before and after the alkaline flushing of the membrane is tested and calculated.
[0044] The contact angle of the prepared nanofiltration membrane surface was measured using the Dataphysics OCA25 video optical contact angle tester. Drop water on the surface of the nanofiltration membrane, and measure the contact angle of the water drop on the membrane surface to characterize the hydrophilicity and hydrophobicity of the membrane material. The smaller the contact angle value, the better the hydrophilicity of the membrane surface. To ensure the accuracy of the analysis results, the membrane was tested more than 5 times at different positions and the average value was taken. The test conditions are as follows: ambient temperature: 23.0±2.0℃, relative humidity: 50%±5%.
[0045] Example 1
[0046] The polysulfone-based membrane is immersed in a mixed aqueous phase solution containing 1.5wt% PIP and 0.03wt% carboxyl nitrile latex with a molecular weight of 30,000 for 2 minutes, and then the liquid on the membrane surface is separated and removed, and then immersed in a n-decane oil phase solution containing 0.15wt% TMC and 0.3wt% epoxy-polyethylene glycol-epoxy with a molecular weight of 3000 for interfacial polymerization reaction, and the reaction time is 10 minutes in an oven at 150°C to obtain a polysulfone-based membrane covered with a polypiperazineamide layer;
[0047] Example 2
[0048] The difference between this embodiment and embodiment 1 is that the molecular weight of the carboxyl nitrile latex in the aqueous phase solution is 10,000.
[0049] Example 3
[0050] The difference between this embodiment and embodiment 1 is that the molecular weight of the carboxyl nitrile latex in the aqueous phase solution is 50,000.
[0051] Comparative Example 1
[0052] The difference between this embodiment and embodiment 1 is that the molecular weight of the carboxyl nitrile latex in the aqueous phase solution is 5000.
[0053] Comparative Example 2
[0054] The difference between this embodiment and embodiment 1 is that the molecular weight of the carboxyl nitrile latex in the aqueous phase solution is 60,000.
[0055] Comparative Example 3
[0056] The difference between this embodiment and embodiment 1 is that no carboxyl nitrile latex is added to the aqueous phase solution, and no epoxy-polyethylene glycol-epoxy is added to the oil phase solution.
[0057] Comparative Example 4
[0058] The difference between this embodiment and embodiment 1 is that no carboxyl nitrile latex is added to the aqueous phase solution.
[0059] Example 4
[0060] The difference between this embodiment and embodiment 1 is that the concentration of carboxyl nitrile latex in the aqueous phase solution is 0.01%.
[0061] Example 5
[0062] The difference between this embodiment and embodiment 1 is that the concentration of carboxyl nitrile latex in the aqueous phase solution is 0.05%.
[0063] Table 2 Nanofiltration membrane performance test of Examples 1 to 5 and Comparative Examples 1 to 4
[0064]
[0065] From the test results in Table 2, it can be seen that when the molecular weight of carboxyl nitrile latex is between 10000 and 50000, the comprehensive performance of the nanofiltration membrane is the best, with a higher desalination rate and membrane flux. In addition, for the accelerated acid and alkali resistance experiments, the desalination performance can be well maintained stable, with a flux greater than 45LMH, a desalination rate greater than 98.5%, and a retention rate decrease of less than 1.5% after acid and alkali cleaning.
[0066] Example 6
[0067] The difference between this embodiment and embodiment 1 is that the molecular weight of the epoxy-polyethylene glycol-epoxy in the oil phase solution is 1000.
[0068] Example 7
[0069] The difference between this embodiment and embodiment 1 is that the molecular weight of the epoxy-polyethylene glycol-epoxy in the oil phase solution is 5000.
[0070] Comparative Example 5
[0071] The difference between this embodiment and embodiment 1 is that the molecular weight of the epoxy-polyethylene glycol-epoxy in the oil phase solution is 500.
[0072] Comparative Example 6
[0073] The difference between this embodiment and embodiment 1 is that the molecular weight of the epoxy-polyethylene glycol-epoxy in the oil phase solution is 6000.
[0074] Comparative Example 7
[0075] The difference between this embodiment and embodiment 1 is that the epoxy-polyethylene glycol-epoxy in the oil phase solution is replaced by diepoxybutane.
[0076] Example 8
[0077] The difference between this embodiment and embodiment 1 is that the concentration of epoxy-polyethylene glycol-epoxy in the oil phase solution is 0.1%.
[0078] Example 9
[0079] The difference between this embodiment and embodiment 1 is that the concentration of epoxy-polyethylene glycol-epoxy in the oil phase solution is 0.5%.
[0080] Table 3 Nanofiltration membrane performance test of Examples 6 to 9 and Comparative Examples 5 to 7
[0081]
[0082] From the test results in Table 3, it can be seen that when the molecular weight of epoxy-polyethylene glycol-epoxy is between 1000 and 5000, the comprehensive performance of the nanofiltration membrane is the best. While epoxy-polyethylene glycol-epoxy plays the role of a cross-linking agent, the ether oxygen of epoxy-polyethylene glycol-epoxy has a non-shared electron pair, which can form a hydrogen bond with the free amine group on the amide bond, enhancing the stability of the overall structure and further improving the acid and alkali resistance of the nanofiltration membrane.
Claims
1. An acid- and alkali-resistant nanofiltration membrane, comprising a polysulfone porous support layer and a polyamide separation layer formed on the support layer; wherein: The separation layer is made by interfacial polymerization of a water phase containing aliphatic polyamine and carboxyl nitrile latex and an organic phase containing aromatic polyacyl chloride and epoxy-polyethylene glycol-epoxy; The number average molecular weight of the carboxyl nitrile latex is 10,000 to 50,000; the number average molecular weight of the epoxy-polyethylene glycol-epoxy is 1,000 to 5,000.
2. The acid- and alkali-resistant nanofiltration membrane according to claim 1, characterized in that: The number average molecular weight of the epoxy-polyethylene glycol-epoxy is 2000-4000.
3. The method for preparing the acid- and alkali-resistant nanofiltration membrane according to claim 1, comprising the following steps: 1) preparing the aqueous phase: uniformly mixing the aliphatic polyamine, the carboxyl nitrile latex and water to obtain an aqueous phase solution; 2) preparing the oil phase: mixing the aromatic polyacyl chloride, epoxy-polyethylene glycol-epoxy and an organic solvent to obtain an oil phase solution; 3) Interfacial polymerization reaction: the polysulfone porous support layer is first contacted with the aqueous solution for 2 to 10 minutes, and then contacted with the oil phase solution after removing the excess solution on the surface, and placed in an oven at 100 to 180° C. for 5 to 20 minutes to allow the epoxy to fully react with the amino group and the carboxyl group, and then dried to obtain the nanofiltration membrane.
4. The method according to claim 3, characterized in that In the aqueous phase solution, the mass concentration of the aliphatic polyamine is 1-2.5%; and / or the aliphatic polyamine is selected from one or more of piperazine, ethylenediamine, triethylenetetramine, tetraethylenepentamine and aminoethylpiperazine.
5. The method according to claim 4, characterized in that In the aqueous phase solution, the mass concentration of the aliphatic polyamine is 1.2-1.5%.
6. The method according to claim 3, characterized in that In the aqueous phase solution, the mass concentration of the carboxyl nitrile latex is 0.01-0.05%.
7. The method according to claim 3, characterized in that In the aqueous phase solution, the mass concentration of the carboxyl nitrile latex is 0.02-0.04%.
8. The method according to claim 3, characterized in that In the oil phase solution, the mass concentration of the aromatic polyacyl chloride is 0.1-0.25%; and / or the aromatic polyacyl chloride is selected from one or more of trimesoyl chloride, phthaloyl chloride and isophthaloyl chloride.
9. The method according to claim 8, characterized in that In the oil phase solution, the mass concentration of the aromatic polyacyl chloride is 0.15-0.2%.
10. The method according to claim 3, characterized in that In the oil phase solution, the mass concentration of epoxy-polyethylene glycol-epoxy is 0.1-0.5%.
11. The method according to claim 3, characterized in that In the oil phase solution, the mass concentration of epoxy-polyethylene glycol-epoxy is 0.2-0.4%.
12. The method according to claim 3, characterized in that The organic solvent is selected from one or more of n-hexane, n-heptane, n-decane, Isopar L and Isopar G isomeric alkanes.
Citation Information
Patent Citations
Crosslinked cellulosic nanofiltration membranes
CN102921310A
Nanofiltration membrane as well as preparation method and application thereof
CN104548970A
Composite nanofiltration membrane and preparation method thereof
CN105435656A
A high-desalination reverse osmosis membrane containing a polyethylene glycol epoxide coating
CN111001311B
Preparation method of modified polytetrafluoroethylene nanofiltration membrane and prepared nanofiltration membrane
CN112495192A